Friction and Wear Analysis of UHMWPE Material Using Pin-on-Disc Tester with Lubricant and Non-Lubricant. (July 2020) - Wahyudi, M; Ismail, R; Jamari, J
Abstract: Ultra-high molecular weight polyethylene (UHMWPE) is a biomaterial that is widely used in the manufacture of acetabular liners for the application of artificial hip joints (AHJ). The problem that often arises from UHMWPE material is the occurrence of wear debris as a result of the mechanism of contact of UHMWPE material with its partner material on AHJ. The purpose of this research is to analyze the friction and wear behavior of UHMWPE material which is paired with AISI 316L. Wear test using a pin-on-disc tribometer in dry conditions and serum bovine lubricant. SEM-EDX analysis is used to see the phenomenon of wear track and absorption of AISI 316L metal elements that occur in UHMWPE. The results showed that the use of bovine serum significantly decreased the friction and wear rates of the UHMWPE / AISI 316 pair.